ASSESSMENT OF EFFICIENCY OF ORGANIZATIONAL CHANGES - Malvina Gyulnezerova (Вестник Северо-Кавказского федерального университета, 2022)
In article concepts of organizational changes and organizational development are considered, the principles of an assessment of efficiency of organizational changes, mechanisms ofplanning of organizational changes, the main techniques of carrying out reorganizations in the organizations are analyzed. In article examples of the planned and unplanned changes happening at the enterprise are given.